Lets get active: learning about Birds - Chowdhary, Eman (New Delhi The Energy and Resource Institute, 2014)
Learning about Birds educates young learners about birds in an interesting, fun-filled format. It explains fascinating facts about blue jay, ostrich, dodo, and many more birds through various spot-the-difference, maze, dot-to-dot, and colouring activities, besides simple counting and writing exercises. Its easy-to-do, illustrated activities promote creative thinking and problem solving among young minds, making the title a fun supplement to their textbooks, while introducing them to nature through the world of birds.
Keywords: Birds; Activity book